2018
DOI: 10.1002/star.201700299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biocomposite Edible Coatings Based on Pea Starch and Guar Gum on Nutritional Quality of “Valencia” Orange During Storage

Abstract: The application of environmentally friendly components is an approach for substitution of synthetic substances in commercial waxes applied to citrus. In this study, the effect of biocomposite edible coatings based on pea starch and guar gum (PSGG) on total vitamin C, phenolic, flavonoid, anthocyanins, and carotenoid content, and antioxidant capacity of “Valencia” orange stored at 5 and 20 °C for 4 weeks are evaluated. The fruits are coated by a single layer PSGG coating, blended composite PSGG coating containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In the food industry, a combination of starch and gums is used to modify and control texture, improve moisture retention and control water mobility [259]. Guar gum and pea starch edible coatings provided effective control in ethylene production, respiration rate and weight and firmness loss [260]. In peach fruit, tara gum treatments produced a good effect on weight loss reduction, firmness conservation and maintenance of greater total soluble solids [261].…”
Section: Edible Films and Coatings And The Post-harvest Quality Of Vegetables And Fruitsmentioning
confidence: 99%
“…In the food industry, a combination of starch and gums is used to modify and control texture, improve moisture retention and control water mobility [259]. Guar gum and pea starch edible coatings provided effective control in ethylene production, respiration rate and weight and firmness loss [260]. In peach fruit, tara gum treatments produced a good effect on weight loss reduction, firmness conservation and maintenance of greater total soluble solids [261].…”
Section: Edible Films and Coatings And The Post-harvest Quality Of Vegetables And Fruitsmentioning
confidence: 99%
“…Babatola and Ibukunolu (2020) observed a significant difference in the ascorbic acid content of tomatoes stored on open shelves and in the refrigerator. The conversion rate of organic acids in samples without packaging was higher than in packaged samples, associated with an increased respiration rate during storage (Saberi et al, 2018). TPC Two-way ANOVA showed significant effects and interactions (p<0.05) between the two factors on TPC (Table 3) only on day 8 in cherry tomato.…”
Section: Ascorbic Acid Contentmentioning
confidence: 90%
“…The ndings of this study were like the results reported in previous studies. 25,40 Titratable acidity (TA). Titratable acidity (TA) decreases during ripening of fruit due to the conversion of organic acids into sugar; however coating on fruit can effectively slow down the respiratory process resulting in a reduced rate of conversion of organic acids, as organic acids are used as substrates for respiratory metabolism.…”
Section: Effects Of Coating Treatment On the Quality Of The Citrus Fr...mentioning
confidence: 99%